Surgical Risk and Pathological Results of Emergency Resection in the Treatment of Acutely Obstructing Colorectal Cancers: A Retrospective Cohort Study - Giovanni Domenico Tebala; Andrea Mingoli; Andrea Natili; Abdul Qayyum Khan; Gioia Brachini (Annals of Coloproctology, 2021)
Purpose The treatment of acutely obstructing colorectal cancers is still a matter of debate. The prevailing opinion is that an immediate resection should be performed whenever possible. This study sought to determine whether immediate resection is safe and oncologically valid. Methods We completed a retrospective 2-center cohort study using the medical records of patients admitted for acutely obstructing colorectal cancer under the care of the Colorectal Team, Noble’s Hospital, Isle of Man, and the Emergency Surgery Unit, Umberto I University Hospital, Rome, from March 2013 to May 2017. The primary endpoints were 90-day mortality and morbidity, reoperation rate, and length of stay. The secondary endpoints were status of margins, number of lymph nodes retrieved, and the rate of adequate nodal harvest. Results Sixty-three patients were retrospectively enrolled in the study. Mortality was associated with age > 80 years and Dukes B tumors. The length of hospital stay was shorter in patients who had their resection less than 24 hours from their admission, in those who had laparoscopic resection and in those with distal tumors. The number of lymph nodes retrieved and rate of R0 resections were similar to those reported in elective colorectal surgery and were greater in laparoscopic resections and in patients operated on within 24 hours, respectively. Conclusion Immediate resection is a safe and reliable option in patients with acutely obstructing colorectal cancer.